Pengembangan Game Platformer 2D Menggunakan Teknik Projection Mapping - Monel Lindu Sagala; Eriq M. Adams Jonemaro; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Augmented reality is one of the new trend in the way of playing game and pretty popular among video game fans nowadays. Augmented reality become pretty popular among video game mainly because the high level of interactivity and immersivity for the game that using augmented reality. One of the technique that can be used in playing video game is projection mapping technique. Because all of that, in this thesis' project, the 2D platformer game developed with projection mapping technique. This game designed with methods such as game's formal elements, which in turn digital prototype to be used as metod to develop the game's prototype. Based on the result of functionality testing using basis path testing, it can be shown that functionality of 2D platformer game are running well. Based on the gameplay testing can be concluded that 2D platformer game that has been developed with projection mapping technique is pretty interesting, interactive, and immersive.